Gestion des déchets dangereux et responsabilité sociale des firmes : le commerce illégal de déchets électriques et électroniques - Faouzi Bensebaa; Fabienne Boudier (Développement Durable et Territoires)
Based on the analysis of the waste electrical and electronic equipments (WEEE), the research investigates the motivations for the illegal cross-border trade in hazardous wastes from developed countries to developing countries. Although many developed countries have implemented waste shipment regulations, they are passing the risks and costs of E-waste to developing countries. Indeed, E-waste is often sent for recycling and refurbishing in developing countries. The two-side proposed approach (i.e. economical and institutional) suggests that both the cost for firms to comply with increasing regulations and the imperfect implementation of regulatory restrictions lead to socially irresponsible behaviours. An increasing and better involvement of stakeholders may be put forward as a solution.